PENGARUH PERSEPSI, MOTIVASI, SELF EFFICACY TERHADAP MINAT BERKARIR MAHASISWA AKUNTANSI DI BIDANG PERPAJAKAN - darmita; Br. Purba, Neni Marlina (SCIENTIA JOURNAL, 2022)
Education is a form of manifestation of dynamic human art and culture and a condition for development. The increasing demand in the world of work triggers today's children to continue their education in tertiary schools. In Indonesia, the accounting study program is one of the most popular study programs when accepting new students on campus. The potential for a profession in the tax sector such as a tax consultant can certainly increase if you see the large number of accounting students in Batam City. However, this is in stark contrast to the number of tax consultants in Batam City. This study aims to determine whether factors such as Perception, Motivation and Self-Efficacy can influence students' career interests in the field of taxation. This research was conducted at universities in Batam City. student career interest in the field of taxation. while Motivation has no effect on student career interest in taxation.